RENTAL APPLICATION AND RETURN LIBRARY BOOKS STMIK JAKARTA STI & K USING MICROSOFT VISUAL FOXPRO 9.0 - Verani Amaliah; Sutarno, SKom, MMSI Sutarno, SKom, MMSI (Jurnal Sistem Informasi, 2010)
Advances in technology increasingly fast computers that have a positive impact in various fields of work. Work processes that still use the manual process can be computerized so that the deficiencies  and weaknesses that occurred in the manual process can be minimized. Writing this research study about borrowing procedures and library book return on STI & K. STMIK JAKARTA This application is expected to optimize library services and provision of information, especially on the lending transaction and return books. This application can mengotrol borrow and return books, providing convenience in the calculation of penalties if the borrower's late return of books and provides printing transaction reports loaning and book return.